Hubungan status gizi dengan perkembangan mental dan psikomotor anak usia 12 sampai 24 bulan di daerah endemis GAKI - Sri Desfita; Toto Sudargo; Maria Goretti Adiyanti (Jurnal Gizi Klinik Indonesia, 2007)
Background: Malnutrition is one of major public health problem in Indonesia. Prevalence of malnutrition in Indonesia in 2005 was 23.8% and in the Province of Yogyakarta Special Territory in 2002 was 15%. District of Sleman had prevalence of malnutrition as much as 11.39% and Cangkringan as one of heavy iodine deficiency disorder endemic areas at district level had 12.5% of malnutrition prevalence. Children at iodine deficiency disorder endemic areas might likely have growth and development disorder.Objective: To identify relationship between nutritional status and mental psychomotoric development of children of 12 to 24 months old at iodine deficiency disorder endemic areas.Method: The study was observational with cross sectional design carried out at Subdistrict of Cangkringan, District of Sleman. Subjects of the study were 75 children aged 12–24 months chosen by using consecutive sampling technique. Dependent variables of the study were mental and psychomotoric development, independent variable was nutritional status of children based on anthropometry with length/age indicator. Confounding variables were birth weight, mothers’ iodine status, level of education, job and family economic status. Other independent variable affecting nutritional status of children was mothers’ height. Data were analysed using chi square, Fisher’s exact test, and independent t-test.Results: Prevalence of low nutritional status was 13.33%. Children with normal nutritional status had average mental development index (MDI) 2.49 points and psychomotoric development index (PDI) 5.37 points higher than those with low nutritional status. However, relationship between nutritional status and mental and psychomotoric development was statistically insignificant.Conclusion: Relationship between nutritional status and mental and psychomotoric development of children of 12–24 months old was not statistically significant. Children with normal nutritional status tended to have higher MDI and PDI score than those with low nutritional status.